The Effect of Scrapbook Media on Knowledge of Dental and Oral Health Care in Grade 3 Students at SD Negeri 110 Palembang - Masayu Nurhayati; Suci Oktaviana; Puja Alfathiya; Dita Sukmawati (Formosa Journal of Science and Technology, 2023)
Dental health education is an effort to improve dental and oral health from an early age, using modified scrapbook media. The aim of the study was to analyze the effect of scrapbook media on children's skill knowledge. This research method uses a quasi- experiment (pseudo-experiment) with pre-test and post-test treatment. Sampling by stratified random sampling method consisting of 30 respondents at SDN 110 Palembang. The independent variable is the scrapbook media. The dependent variable is knowledge about oral health. Data were analyzed using the Paired t-test of 9.9. Based on the analysis of the Paired t-test, a significance value of 9.9 was obtained. The results of the study concluded that scrapbook media influences the increase in dental and oral health knowledge in children. The conclusion is that there is an increase in knowledge of dental and oral hygiene.